2023
DOI: 10.1101/2023.01.20.23284842
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The safety and relative effectiveness of non-psychoactive cannabinoid formulations for the improvement of sleep: a double-blinded, randomized controlled trial

Abstract: The objective of this randomized, double-blinded controlled trial was to evaluate the safety and relative effects of different formulations containing Cannabidiol (CBD) and melatonin, with and without the addition of minor cannabinoids, on sleep. Participants (N=1,793 adults experiencing symptoms of sleep disturbance) were assigned to receive a 4-week supply of 1 of 6 products (all capsules) containing either 15mg CBD or 5mg melatonin, alone or in combination with minor cannabinoids. Sleep disturbance was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The exact mechanisms underlying the impact of CBD on the body remain unclear; however, they interact with serotonin receptors and modulate CB1 receptor activation, potentially influencing anxiety-related brain structures ( 4 , 24 ). The results regarding the effects of CBD on sleep are inconsistent, with studies showing varied outcomes ( 25 , 26 , preprint; 27 , 28 ). Notably, lower CBD doses (18–25 mg) demonstrated positive effects on anxiety and sleep in retrospective studies and individual patient case reports ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanisms underlying the impact of CBD on the body remain unclear; however, they interact with serotonin receptors and modulate CB1 receptor activation, potentially influencing anxiety-related brain structures ( 4 , 24 ). The results regarding the effects of CBD on sleep are inconsistent, with studies showing varied outcomes ( 25 , 26 , preprint; 27 , 28 ). Notably, lower CBD doses (18–25 mg) demonstrated positive effects on anxiety and sleep in retrospective studies and individual patient case reports ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, there appears to be a dose-response effect of CBD supplementation on sleep, with higher doses inducing a sedative effect and lower doses promoting alertness [ 23 ]. In a study investigating the impact of CBD on sleep among adults with sleep disturbances, more than half of the 1,793 participants improved sleep quality following the administration of 15 mg CBD over five weeks [ 24 ]. Several studies have demonstrated the sedative effects of CBD in clinical populations, however, more evidence is needed in healthy populations.…”
Section: Introductionmentioning
confidence: 99%